Carotid Endarterectomy for the Treatment of Carotid Near-Occlusion With Recurrent Symptoms - Zhang, Jianbin; Chen, Jie; Xu, Xiaojie; Sun, Mingsheng; Chen, Shu; Liu, Peng; Ye, Zhidong (Frontiers in Neurology, 2022)
Objective: Report our preliminary experience of carotid endarterectomy (CEA) for the treatment of carotid near-occlusion (CNO) with recurrent symptoms. Materials and methods: Retrospectively analyze the demographics, treatment detail and outcomes data of 122 CNO patients from 2014 to 2020. According to whether distal full collapse exist, patients were classified into full collapse group and non-full collapse group. The incidence of death, myocardial infarction, stroke and other variables were compared between the 2 groups. Results: 122 patients with CNO and recurrent symptoms were enrolled. The demographics was comparable between the 2 groups. 30-day incidence of primary endpoints was 1.85% in full collapse group and 4.41% in non-full collapse group. 12-month incidence of primary endpoints was 7.41% in full collapse group and 4.41% in non-full collapse group. 1 re-stenosis occurred in non-full collapse groups 8 months after CEA. Conclusion: For carotid near-occlusion patients with recurrent symptoms, carotid endarterectomy is safe and effective despite of whether distal full collapse exist. Shunt is important to avoid intraoperative hypoperfusion and postoperative hyperperfusion. The long-term results should be further evaluated.